Thrombotic Aortic Restenosis After Transapical SAPIEN Valve Implantation. Issue 2 (13th December 2013) - Pergolini, Amedeo; Pino, Paolo Giuseppe; Zampi, Giordano; Polizzi, Vincenzo; Musumeci, Francesco
Abstract We describe a patient previously implanted with a SAPIEN Edwards valve by the transapical approach, who subsequently experienced a valve thrombosis. The literature on this subject is reviewed. doi: 10.1111/jocs.12275 (J Card Surg 2014;29:204–208)